The Bombo (drum) instrument ensemble and drum music tradition of the Ati indigenous community in Iloilo - Taton, Jose, Jr.; Rola, Salveo (2022)
The bombo (drum) instrument ensemble is considered an important facet of the music culture of the Ati indigenous community in Iloilo. As music objects and as a type of sound practice, the bombo plays significant roles in Ati society. This paper, thus, looks into two interrelated dimensions in bombo practice – the drum (1) as material culture and the drum (2) as a socio-historical object. In the first aspect, we discuss the function, composition, and construction technology of the ensemble as well as discuss musical performances associated with the drums. In the second aspect, we look into how the bombo as objects become embedded into the social fabric of Ati life. Along these lines, we posit that the bombo, as a tangible material and as a musical practice, plays an integral role in the musical, social, and cultural milieu of Ati society as the community navigates within and across traditional and contemporary music spaces.
Keywords: Instrumental music; Drums (Musical instruments); Music & culture